Pengembangan e-LKPD Larutan Penyangga Berbasis Guided Inquiry Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Liza Meri Oktavia; Wilda Syahri; Asmi yunda (Mathematics Education Study Program, 2025)
This study aims to develop a guided inquiry-based buffer solution e-LKPD to improve students' critical thinking skills. e-LKPD is designed to be more interesting, interactive and practical by utilizing digital technology in learning. The development model used is the Lee & Owens development model, with 5 stages: analysis, design, development, implementation, and evaluation. The research instruments include teacher interview sheets, student needs questionnaires, material expert validation questionnaires, media expert validation questionnaires, teacher assessments and student response questionnaires. The trial was conducted on 10 grade XI phase F students. The results of the e-LKPD development research were declared valid and suitable for use in learning. The assessment by the material validator obtained a score of 0.83 in the feasible category. The media validator gave a score of 0.87 in the feasible category. The teacher's assessment showed a score of 4.3 included in the very feasible category. The trial to students showed a level of effectiveness with an N-gain value of 0.61 in the moderate category. Students gave a positive response with a value of 88% in the very good category. This guided inquiry-based e-LKPD has been proven to be valid, feasible and effective in improving students' critical thinking skills.